Pengaruh Kualitas Kehidupan Kerja Terhadap Kinerja Karyawan Pada PT. Bank Sulut Kantor Pusat - Anggy Susana Mukuan; Sontje Sumayku; Sonny Kaparang (JURNAL ADMINISTRASI BISNIS, 2014)
Quality of Work Life is a management system approach to coordinating and connecting the potential of Human Resources, where the quality of work life in the organization as a leader of the effort to meet the needs of members and organizations simultaneously and continuously. This study aims to determine whether the effect on Quality of Work Life Employee Performance PT. Flammable Bank Headquarters. This study used a quantitative approach, which becomes the main variable in this study is the Quality of Work Life (X) Employee Performance (Y). In this study population was 150 employees of PT. Bank of North Sulawesi with inaccuracy rate of 10%, the sample size in this study was 60 people through a calculation using the formula Slovin. From the results of successful data obtained through questionnaires, and calculated using simple regression analysis and simple correlation has been obtained significant data. After analyzing the correlation and regression method was then tested this hypothesis in hypothesis testing using t testing. in testing the t test assumed that reject Ho tcount > ttable and accept Ha if tcount<ttable. Having formulated the formula so that the result of t-test, t-test is 5.3454. After getting significant results with ttable tcount tested for 5% error level test two parties and dk= n-2 will be obtained ttable 1.67. So based on t = 5.3454 and 1.67, the ttest>ttable= 5.3454> 1.67. The results of the calculations between the quality of work life on employee performance with regression analysis showed that the quality of work life affects the performance of employees at PT. Bank Of North Sulawesi. Â  Keywords: Quality of Work Life, Employee Performance.